Advancement in Green Synthesis of Titanium Dioxide : Photocatalytic and Larvicidal Activities – A review - Deliza, Deliza; Safni, Safni; Zein, Rahmiana; Putri, Reza Audina (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Nanotechnology is a fast expanding field with several applications in science, engineering, healthcare, pharmaceutical, and other areas. Nanoparticles (NP) are frequently produced through a variety of physical and chemical methods. Recently, green synthesis technologies that are more simple, sustainable, and cost-effective have been developed. The environmentally friendly/sustainable synthesis of titanium dioxide nanoparticles (TiO2 NPs) has been in great demand in the previous quarter. Bioactive components found in organisms, such as plants, facilitate the processes of bio-reduction and restriction. This review described green synthesis of TiO2 NPs, the photocatalytical uses, and managing the larvicidal activity of disease-spreading mosquitoes. Various natural reducing agents including proteins, enzymes, phytochemicals, and others, are involved in the synthesis of TiO2 NPs. Current research findings and future concerns in a viable platform based on biologically meditated TiO2 nanostructures for industrial applications.